2019
DOI: 10.1021/acs.jpclett.9b01565
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Transition States during the Hydration of Clay Minerals

Abstract: A molecular-scale understanding of the transition between hydration states in clay minerals remains a challenging problem because of the very fast stepwise swelling process observed from X-ray diffraction (XRD) experiments. XRD profile modeling assumes the coexistence of multiple hydration states in a clay sample to fit the experimental XRD pattern obtained under humid conditions. While XRD profile modeling provides a macroscopic understanding of the heterogeneous hydration structure of clay minerals, a micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 64 publications
5
84
1
Order By: Relevance
“…This evidence that energetic barriers to swelling or dehydration are relatively weak beyond the 2-layer hydrate is consistent with MD simulation predictions of the free energy of swelling of a pair of Na-smectite nanoparticles in bulk liquid water. 104 The results presented above validate various experimental hypotheses based on calorimetric, X-ray diffraction, and gravimetric water sorption experiments regarding the ordering of hydration and dehydration and the coexistence of different hydration environments in smectite films. 42,43,96,105−109 Specifically, our results show that smectite dehydration proceeds through the following sequence of partially overlapping steps:…”
Section: ■ Introductionsupporting
confidence: 75%
“…This evidence that energetic barriers to swelling or dehydration are relatively weak beyond the 2-layer hydrate is consistent with MD simulation predictions of the free energy of swelling of a pair of Na-smectite nanoparticles in bulk liquid water. 104 The results presented above validate various experimental hypotheses based on calorimetric, X-ray diffraction, and gravimetric water sorption experiments regarding the ordering of hydration and dehydration and the coexistence of different hydration environments in smectite films. 42,43,96,105−109 Specifically, our results show that smectite dehydration proceeds through the following sequence of partially overlapping steps:…”
Section: ■ Introductionsupporting
confidence: 75%
“…This behavior contrasts with ion diffusion-limited exchange in anhydrous phyllosilicates (11), which increases appreciably with temperature through the Arrhenius behavior of the diffusion coefficient (12). Interlayer water diffusion has a strong temperature dependence (13), while species exchange, including water, between bulk solution and the interlayer is essentially barrierless (14,15), indicating that neither process limits collapse.…”
Section: Significancementioning
confidence: 92%
“…We used the Weighted Histogram Analysis Method (WHAM) code (Grossfield) to extract the PMF profile from the umbrella sampling results. Ho et al (2019) showed that the ClayFF parameter set does not predict the dry to onewater layer (0W -1W) hydration process well. The authors of the study modified ClayFF to capture the dry to hydrated state transition.…”
Section: Coulombic Interactions Are Calculated Usingmentioning
confidence: 99%